2017
DOI: 10.20849/ijsn.v3i1.356
|View full text |Cite
|
Sign up to set email alerts
|

Maternity Nurses’ Performance Regarding Cardiopulmonary Resuscitation During Pregnancy: Simulation Based Intervention

Abstract: Background: Training maternity nurse regarding cardiopulmonary resuscitation during pregnancy is most important for properly care of such emergency situations during pregnancy and save woman’s and fetal lives.The aim of the present study was to evaluate effect of simulation-based intervention on maternity nurse’ performance regarding cardiopulmonary resuscitation during pregnancy. Design Aquasi-experimental design was adopted in the current study.The study was conducted at woman’s health nursing department tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…These findings were highly supported by (15). who reported that women knowledge regarding signs & symptoms of rheumatic heart disease during pregnancy was in adequate and recommended educational guidelines for pregnant women, there was a high statistical significant improvement in women's knowledge about rheumatic heart diseases during pregnancy at post educational guidelines and follow up phases of the application of the educational guidelines (p-value < 0.01).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These findings were highly supported by (15). who reported that women knowledge regarding signs & symptoms of rheumatic heart disease during pregnancy was in adequate and recommended educational guidelines for pregnant women, there was a high statistical significant improvement in women's knowledge about rheumatic heart diseases during pregnancy at post educational guidelines and follow up phases of the application of the educational guidelines (p-value < 0.01).…”
Section: Discussionsupporting
confidence: 54%
“…This result disagree with (13) in their study done in Baghdad they revealed that one third of studied pregnant women only were always receiving knowledge regarding heart disease during pregnancy. Similarly to (14) , reported that approximately one third of studied pregnant women had correct knowledge about complication of heart diseases during pregnancy.…”
Section: Discussionmentioning
confidence: 94%